2015
DOI: 10.1002/app.42397
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of microfibrillated cellulose‐reinforced thermoplastic starch composites

Abstract: In this study thermoplastic starch (TPS) matrix-based microfibrillated cellulose (MFC) reinforced microcomposites were prepared via extrusion compounding in one-step. Starch was plasticized with a combination of glycerol and water. The native starch/glycerol and the plasticized starch/water ratios were set for 4/1 and 6/1, respectively. Two different MFC types (of varying mean length and diameter) were incorporated up to 20 wt.% in the plasticizer-containing premix prior to its compounding in a twinscrew extru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…Melt processing has been employed in numerous research projects in which nanocellulose was used as a minor component to reinforce a thermoplastic resin (Seydibeyoglu and Oksman 2008;Martínez-Sanz et al 2012, 2013aSuzuki et al 2013Suzuki et al , 2014Fortunati et al 2014;Ambrosio-Martin et al 2015a;Arrieta et al 2015;Ferrer et al 2016a;Herrera et al 2016;Lendvai et al 2016). After emerging from the die of the extruder, the material cools below the melting point of the matrix polymer.…”
Section: Melt Extrusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melt processing has been employed in numerous research projects in which nanocellulose was used as a minor component to reinforce a thermoplastic resin (Seydibeyoglu and Oksman 2008;Martínez-Sanz et al 2012, 2013aSuzuki et al 2013Suzuki et al , 2014Fortunati et al 2014;Ambrosio-Martin et al 2015a;Arrieta et al 2015;Ferrer et al 2016a;Herrera et al 2016;Lendvai et al 2016). After emerging from the die of the extruder, the material cools below the melting point of the matrix polymer.…”
Section: Melt Extrusionmentioning
confidence: 99%
“…Relatively low-melting polymers are often preferred in order to avoid thermal damage to the cellulosic reinforcement during compounding. Alternatively, researchers who want to utilize nature-based products have selected poly-(lactic acid) (Martínez-Sanz et al 2012) or thermoplastic starch mixtures (Lendvai et al 2016) as the matrix. Herrera et al (2016) showed that the results were strongly affected by the rate of cooling in the case of poly-lactic acid film reinforced with CNC.…”
Section: Melt Extrusionmentioning
confidence: 99%
“…On other hand, in last decades, different kinds of additives such as antioxidants, antimicrobials, nutrients, or flavors were incorporated in starch films to give them greater benefices . This, either to transfer their properties to the food they cover or to enrich the consumer if they want to eat the film.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them study the influence of fiber type and amount usually by determining properties at one or two fiber contents. All kinds of fibers have been used as filler in TPS including various forms of cellulose [6,[12][13][14][15][16][17][18][19][20][21][22][23][24], jute [18,[25][26][27], sisal [28][29][30][31][32][33], wheat straw [13], flax [23,34] hemp [13,28,35,36], cotton [13,37,38], flax [19,39], ramie [20,40].…”
Section: Introductionmentioning
confidence: 99%